GEOMETRIC PUZZLE AND ART THERAPY (PLATE ART COLLAGE) TO IMPROVE CONCENTRATION AND SOCIAL INTERACTION OF MENTALLY RETARDED CHILDREN AT BC YATIRA SPECIAL SCHOOL - Megasari, Mona; Riyanto, agus (JURNAL KESEHATAN KARTIKA, 2024)
Background: Mental retardation is an underdevelopment of intellectual functioning and adaptive behavior, which occurs during a child’s development. One of the disorders of mentally retarded children is difficulty concentrating. Mentally retarded children also have relatively minimal interaction, as they are unable to have two-way communication with their peers and other people. Objective: to improve children’s concentration and social interaction using Geometric Puzzle and Art Therapy (Plate Art Collage). Methods: This research design uses pre-experimental one group pre-post test. The total sample was 24 people according to the inclusion criteria through the total sampling technique. Data collection using the Attention Checklist (ACL) questionnaire and Social Skills Rating Scales-Teacher Form (SSRS-T). Statistical tests used to analyze data are McNemar test and Wilcoxon Signed Rank Test. Results: Based on the results of the analysis in measuring concentration before and after intervention (p=0.002), and the results of the analysis in measuring social interaction before and after intervention (p=0.001). Conclusion: It can be concluded that geometric puzzle play therapy and art therapy (plate art collage) have a significant effect on concentration and social interaction in mentally retarded children. Through this study, it is hoped that future researchers can assess the speed and reasoning of mentally retarded children in relation to the activities carried out.